Counseling blood donors seropositive for human T-lymphotropic virus types I and II in a developing country - Passos Valéria M. A.; Calazans Fátima F.; Carneiro-Proietti Anna Bárbara F. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
Human T-lymphotropic virus types I and II (HTLV-I/II) are blood-transmitted retroviruses associated with leukemia, myelopathy, and uveitis. From 51,135 eligible blood donors at the Fundação Hemominas tested in 1993, 689 (1.35%) were repeatedly reactive to HTLV-I/II antibodies by enzyme immunoassay and were notified accordingly. Routes of transmission and preventive measures were emphasized in the orientation. Supplementary laboratory tests should be available and free of cost. Health services should recommend the use of latex condoms and make them available. Avoiding shared use of needles or syringes is important for both the seropositive donor and public health in general. In a country with such widespread malnutrition, the benefits of breast-feeding usually outweigh the risks of virus transmission. Based on our experience, we recommend that: 1) identical orientation be given to donors by all health professionals involved in counseling; 2) level of schooling be considered and information provided accordingly; 3) donors be assisted in understanding and assessing available information; 4) psychological assistance be provided to anxious or depressed donors; and 5) joint counseling be offered to donors with stable partners.